Manganese-containing nano material, spray and application of nano material and spray in improvement of nutritional quality of wheat

By synthesizing nanomaterials with manganese -containing elements, nano -spraying agents are prepared and sprayed on wheat plants, solving the problem that the existing technology is difficult to improve the quality of wheat, and achieves high -efficiency and low -cost nutrition quality improvement.

CN119371248APending Publication Date: 2025-01-28TARIM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411503573.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the nutritional quality of wheat, and the existing methods require years of time and a large amount of germplasm resources, increasing the cost of results transformation, promotion and production.

Method used

Through the nano -material materials containing manganese -containing elements through the chemical precipitation method and water thermal method, nano spraying agents are prepared, and sprayed on wheat plants to improve the nutritional quality of wheat.

Benefits of technology

This method can effectively improve the nutritional quality of wheat, reduce the transformation and use cost, suitable for large -scale preparation of industries, and maintain catalytic activity in high temperature, acidic or saline -alkali environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371248A_ABST
    Figure CN119371248A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of agricultural production, and particularly relates to a manganese-containing nanometer material, a spraying agent and application of the spraying agent to improvement of the nutritional quality of wheat. According to the invention, polyacrylic acid (PAA) and manganese sulfate monohydrate are reacted through a chemical precipitation method and a hydrothermal method to synthesize a PAA modified manganese-containing nano material (PMO). The embodiment of the invention shows that the prepared nano material is sprayed at the early growth stage of wheat, and the nutritional quality of wheat grains can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of agricultural production, and specifically relates to a nano material containing manganese element, a spray and application thereof in improving the nutritional quality of wheat. Background Art

[0002] How to improve wheat quality is a difficult problem that affects the global agricultural industry chain. With the improvement of people's living standards, the demand for high-quality special wheat is growing all over the country. Wheat is an important food crop with a large planting area in Xinjiang. Studies have shown that wheat quality is controlled by genetic factors, cultivation measures and environmental factors. As a primary agricultural product, the reduction in wheat quality will undoubtedly reduce the economic benefits of wheat cultivation.

[0003] Plant nanobiology is an emerging interdisciplinary subject with unique ideas for improving wheat quality. Most of the existing methods for improving wheat quality are plant genetic breeding technology, which requires many years and a large amount of germplasm resources. This undoubtedly increases the cost of transformation, promotion and production. Therefore, it is urgent to develop a new method to overcome the shortcomings of existing technologies and improve the nutritional quality of wheat. Summary of the invention

[0004] The purpose of the present invention is to provide a nano material containing manganese element. The method provided by the present invention not only has a simple synthesis method and common equipment, but also has low cost of actual transformation results, and can effectively improve the nutritional quality of wheat.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The invention provides a nano material containing manganese element. The nano material is synthesized from manganese sulfate monohydrate and polyacrylic acid through chemical precipitation method and hydrothermal method.

[0007] The present invention also provides a nano spraying agent, which comprises the above-mentioned nano material.

[0008] Preferably, the spraying concentration of the spraying agent is 100-200 mg / L.

[0009] More preferably, the spray further contains 0.05% by volume of a surfactant.

[0010] The present invention also provides a method for preparing a nano spray agent, which specifically comprises the following steps:

[0011] S1, dissolving manganese sulfate monohydrate and polyacrylic acid in water respectively, and vortexing and mixing the two solutions to obtain a mixed solution;

[0012] S2, adding the mixed solution in step S1 into ammonia water to carry out chemical precipitation reaction and hydrothermal reaction to obtain a reaction product;

[0013] S3, centrifuging the reaction product in step S2, taking the supernatant, dialyzing and filtering to obtain a nanomaterial containing manganese element.

[0014] Preferably, in step S1, manganese sulfate monohydrate and polyacrylic acid are weighed at a mass fraction ratio of 17:180 and dissolved in water to obtain 0.17 g / mL manganese sulfate monohydrate solution and 0.9 g / mL polyacrylic acid solution, respectively.

[0015] Preferably, the mixing condition in step S1 is: 2500rmin -1 Vortex for 15 min.

[0016] Preferably, the chemical precipitation reaction process in step S2 is to add the mixed solution dropwise into 2 times the volume of 30% ammonia water at 25°C and 500 rmin -1 Stir for 24h.

[0017] Preferably, the hydrothermal reaction in step S2 is carried out in a polytetrafluoroethylene-lined reactor at 120° C. for 24 hours.

[0018] The present invention also provides application of the nano material or spraying agent in improving the nutritional quality of wheat grains.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention uses polyacrylic acid and manganese sulfate monohydrate as raw materials and synthesizes a nano-spray fertilizer by chemical precipitation and hydrothermal method, which can be used after simple purification.

[0021] (2) The materials used in the present invention are industrial raw materials with wide applications and moderate prices, and the preparation cost is moderate; the synthesis method is simple, the equipment used is common, suitable for industrial mass production, and easy to transform the results; the actual transformation results have low use costs, high economic benefits and practicality; and can maintain catalytic activity in high temperature, acidic, or saline-alkali environments.

[0022] (3) The nano-spray fertilizer obtained by this method can effectively improve the nutritional quality of wheat. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 The appearance of wheat grains after being treated with different solutions for 33 days;

[0025] Figure 2 This is an analysis chart of the average crude protein content of wheat grains after being treated with different solutions for 33 days;

[0026] Figure 3 This is an analysis chart of the average wet gluten content of wheat grains after being treated with different solutions for 33 days;

[0027] Figure 4 This is an analysis chart of the average hardness of wheat grains after being treated with different solutions for 33 days;

[0028] Figure 5 This is an analysis chart of the average W value of wheat grains after being treated with different solutions for 33 days;

[0029] Figure 6 This is an analysis chart of the average precipitation index of wheat grains after being treated with different solutions for 33 days;

[0030] Figure 7 This is the average falling number analysis chart of wheat grains after being treated with different solutions for 33 days;

[0031] Figure 8 This is an analysis chart of the average capacity of wheat grains after being treated with different solutions for 33 days. DETAILED DESCRIPTION

[0032] The invention provides a nano material (PMO) containing manganese element. The nano material is synthesized from cerium nitrate and polyacrylic acid through chemical precipitation method and hydrothermal method, and finally the PMO modified by polyacrylic acid is obtained.

[0033] The preparation method of the nano material (PMO) of the present invention specifically comprises the following steps:

[0034] S1, dissolving manganese sulfate monohydrate and polyacrylic acid in water respectively, and vortexing and mixing the two solutions to obtain a mixed solution;

[0035] S2, adding the mixed solution in step S1 into ammonia water to carry out chemical precipitation reaction and hydrothermal reaction to obtain a reaction product;

[0036] S3, centrifuging the reaction product in step S2, taking the supernatant, dialyzing and filtering to obtain a nanomaterial containing manganese element.

[0037] In the above step S1, manganese sulfate monohydrate and polyacrylic acid are weighed in a mass fraction ratio of 17:180 and dissolved in water to obtain 0.17 g / mL manganese sulfate monohydrate solution and 0.9 g / mL polyacrylic acid solution, respectively. The mixing conditions in step S1 are: 2500 rmin-1 The chemical precipitation reaction process in step S2 is to add the mixed solution dropwise into 2 times the volume of 30% ammonia water at 25°C and 500 r min -1 The hydrothermal reaction in step S2 is carried out in a polytetrafluoroethylene-lined reactor at 120° C. for 24 hours.

[0038] The invention uses a mixture of a manganese-containing nanomaterial (PMO) and a surfactant (Silwet L-77) to spray on wheat plants; and a pure water control group is set to mix with the surfactant and spray on the wheat plants. The spray concentration of the spray is 100-200 mg / L, and the spray also contains 0.05% by volume of the surfactant.

[0039] At the wheat maturity stage (33 days after treatment), the wheat was threshed and impurities were removed, and the differences in crude protein content, wet gluten content, hardness, W value, sedimentation index, falling number and capacity between the experimental group and the control group were detected and analyzed.

[0040] The wheat variety used in the present invention is the main variety grown in southern Xinjiang: Xindong 55, the seeds of which were purchased from Tahe Seed Industry in Alar City, Xinjiang.

[0041] In order to further illustrate the present invention, the technical solution provided by the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0042] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0043] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.

[0044] Example 1 Preparation of PMO

[0045] 0.425 g of manganese sulfate monohydrate was dissolved in 2.5 mL of double distilled water, and 4.5 g of PAA (MW 1800) was dispersed in 5 mL of double distilled water. The two solutions were stirred at 2500 rmin. -1 Vortex for 15 min to mix thoroughly.

[0046] The mixed liquid was added dropwise into a 30 mL brown ampoule containing 15 mL 30% ammonia water and stirred at 500 rpm on a magnetic stirrer. -1 Stir for 24 h (25° C.).

[0047] The reaction solution was transferred to a 50 mL polytetrafluoroethylene-lined reactor and subjected to hydrothermal reaction at 120 °C for 24 h. After cooling to room temperature, the reaction mixture was heated at 6000 rmin. -1 Centrifuge for 1 hour, take the supernatant, and then dialyze with a dialysis bag (MW 10000) for 24 hours, changing the water every 8 hours, take out and filter, and the colorless liquid is PMO. PMO is finally stored in a refrigerator at 4°C.

[0048] Example 2 Wheat sowing and spraying

[0049] Select wheat seeds with full grains, uniform size and no damage. Set up a test plot with a row length of 3 meters, a row spacing of 20 cm, and a total plot area of ​​3m 2 On October 2, 2023, the seeds were sown in the experimental plot, 2 cm per seed, and watered for 20 minutes after sowing. 3 / mu.

[0050] The wheat was treated on May 14, when it was in the early stage of grain filling. A 100 mg / L nanomaterial mixed solution containing 0.05% Silwet L-77 was evenly sprayed on the middle and upper parts of the wheat in the entire plot using a 5L spraying pot. The wheat was sprayed with pure water containing 0.05% Silwet L-77 as a control group.

[0051] Comparative analysis of Example 3 spraying agent after use

[0052] At the wheat maturity stage, i.e. 33 days after treatment, the treated wheat and the control wheat were harvested, threshed and impurities were removed. The appearance of wheat grains after 33 days of treatment with different solutions was photographed as follows: Figure 1 shown.

[0053] Figure 1 The control group is the control group that applied clean water containing surfactant, and PMO is the treatment group that applied nanomaterials + surfactant. It can be seen from the figure that the grains of the treatment group are fuller in appearance than those of the control group, and the color of some grains is darker than that of the control group, that is, the keratinization is relatively better than that of the control group.

[0054] 3.1 Analysis of crude protein content in wheat grains

[0055] The crude protein content of wheat grains in the experimental group and the control group after 33 days of treatment was measured using a near-infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured three times and the average value was taken. Figure 2 shown.

[0056] The results of crude protein content determination showed that the average crude protein content of wheat grains treated with the spraying agent was significantly higher than that of the control group.

[0057] 3.2 Analysis of wet gluten content in wheat grains

[0058] The wet gluten content of wheat grains in the experimental group and the control group after 33 days of treatment was determined using a near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured 3 times and the average value was taken. The results are shown in Figure 3 shown.

[0059] The results of wet gluten content determination showed that the average wet gluten content of wheat grains treated with the spraying agent was significantly higher than that of the control group.

[0060] 3.3 Analysis of wheat grain hardness

[0061] The hardness of wheat kernel endosperm texture is an important factor affecting wheat flour milling quality and processing quality. It has a great influence on wheat tempering, grinding and sifting processes in the flour making process.

[0062] The hardness of wheat grains in the experimental group and the control group after 33 days of treatment was measured using a near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured 3 times and the average value was taken. The results are shown in the figure. Figure 4 The results of hardness test showed that the average hardness of wheat grains after spraying was not much different from that of the control group.

[0063] 3.4 Analysis of W value of wheat grains

[0064] The W value indicates the "gluten strength" of flour, representing the work used to deform 1 gram of dough in a specified method. Studies have shown that there is a good correlation between the W value and the volume of bread. Different W values ​​are suitable for making different products. The larger the W value, the stronger the gluten, and vice versa.

[0065] The hardness of wheat grains in the experimental group and the control group after 33 days of treatment was measured using a near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured 3 times and the average value was taken. The results are shown in the figure. Figure 5 The results of hardness test showed that the average hardness of wheat grains after spraying with the spraying agent was higher than that of the control group.

[0066] 3.5 Analysis of Sedimentation Index of Wheat Grains

[0067] The wheat sedimentation index is highly correlated with quality indicators such as protein content and wet gluten content, and is one of the important individual indicators reflecting the quality of wheat. A higher sedimentation index indicates high gluten content and good quality, which is conducive to making high-quality bread and other baked products. A lower sedimentation index may mean low gluten content or poor quality, which may affect the texture and taste of pasta.

[0068] The precipitation index of wheat grains in the experimental group and the control group after 33 days of treatment was measured using a near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured 3 times and the average value was taken. The results are shown in Figure 6 The results of sedimentation index test showed that the average sedimentation index of wheat grains treated with the spraying agent was significantly higher than that of the control group.

[0069] 3.6 Falling number analysis of wheat kernels

[0070] Wheat falling index is an important indicator for measuring wheat quality, which reflects the activity of α-amylase in wheat grains. Wheat falling index, also known as falling number, is measured by the total time from the viscometer entering the water heater to the viscometer stirring and falling into the gelatinized suspension, and this time is expressed in seconds. The falling number directly reflects the activity of α-amylase in wheat grains: if the α-amylase activity is low, the falling number is high; conversely, if the α-amylase activity is high, the falling number is low.

[0071] The near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments measured the falling number of wheat grains in the experimental group and the control group after 33 days of treatment. Each group was measured 3 times and the average value was taken. The results are as follows: Figure 7 The results of the falling index test showed that the average falling index of wheat grains treated with the spray agent was not much different from that of the control group.

[0072] 3.7 Analysis of bulk density of wheat grains

[0073] The capacity of wheat grains is one of the important indicators to measure wheat quality. For the same wheat variety, the higher the capacity, the fuller the grain and the higher the flour yield.

[0074] The bulk density of wheat grains in the experimental group and the control group after 33 days of treatment was measured using a near infrared analyzer (SupNIR-1230) produced by Beijing Jitian Instruments. Each group was measured 3 times and the average value was taken. Figure 8 The results of capacity determination showed that the average capacity of wheat grains after spraying was not much different from that of the control group.

[0075] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A nanomaterial containing manganese, characterized in that: The nano material is synthesized from manganese sulfate monohydrate and polyacrylic acid through chemical precipitation method and hydrothermal method.

2. A nano spray agent, characterized in that: The nano spraying agent comprises the nano material according to claim 1.

3. The nano spray agent according to claim 2, characterized in that: The spraying concentration of the spraying agent is 100-200 mg / L.

4. The nano spray agent according to claim 3, characterized in that: The spray also contained 0.05% by volume of a surfactant.

5. A method for preparing a nano spraying agent, characterized in that: The following steps are involved: S1, dissolving manganese sulfate monohydrate and polyacrylic acid in water respectively, and vortexing and mixing the two solutions to obtain a mixed solution; S2, adding the mixed solution in step S1 into ammonia water to carry out chemical precipitation reaction and hydrothermal reaction to obtain a reaction product; S3, centrifuging the reaction product in step S2, taking the supernatant, dialyzing and filtering to obtain a nanomaterial containing manganese element.

6. The method according to claim 5, characterized in that: In the step S1, manganese sulfate monohydrate and polyacrylic acid are weighed at a mass fraction ratio of 17:180 and dissolved in water to obtain 0.17 g / mL manganese sulfate monohydrate solution and 0.9 g / mL polyacrylic acid solution, respectively.

7. The method according to claim 5, characterized in that: The mixing condition in step S1 is: 2500 r min -1 Vortex for 15 min.

8. The method according to claim 5, characterized in that: The chemical precipitation reaction process in step S2 is to add the mixed solution dropwise into 2 times the volume of 30% ammonia water at 25°C and 500 r min -1 Stir for 24h.

9. The method according to claim 5, characterized in that: The hydrothermal reaction process in step S2 is carried out in a polytetrafluoroethylene-lined reactor at 120° C. for 24 hours.

10. Use of the nanomaterial according to claim 1 or the spraying agent according to claim 2 in improving the nutritional quality of wheat grains.